2018
DOI: 10.1016/j.tmp.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding travel constraints: An exploratory study of Mainland Chinese International Students (MCIS) in Norway

Abstract: An exploratory approach using qualitative methodology and 15 in-depth interviews with Mainland Chinese International Students (MCIS) in Norway was employed in the study. The country is experiencing an increasing number of both MCIS and Chinese tourists in general. Passive activities remain as the most popular activities due to travel constraints consisting of lack of information and equipment and the perception of risk due to the lack of perceived skills. Parental disapproval and fear of "losing face" while al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
(97 reference statements)
0
29
0
Order By: Relevance
“…Research showed that [24] LCM could elucidate the perceived travel constraints of multiple tourist segments [5,8]. In this study, we applied [6] revised LCM to evaluate Chinese students' intrapersonal, interpersonal, and structural constraints when studying in Thailand.…”
Section: Survey Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…Research showed that [24] LCM could elucidate the perceived travel constraints of multiple tourist segments [5,8]. In this study, we applied [6] revised LCM to evaluate Chinese students' intrapersonal, interpersonal, and structural constraints when studying in Thailand.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…A clearer understanding of travel constraints would help tourism and destination managers develop adequate promotional strategies for visitors [3]. Studies on travel constraints extended the original leisure constraints model (LCM) [4][5][6] established by [7] to explain perceived travel barriers [6,8,9]. The three basic travel constraints under LCM are intrapersonal constraints, interpersonal constraints, and structural constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive tourism is considered to be the most popular, and may be due to lack of sports equipment, parental consent, and students' sports skills (Mei & Lantai, 2018). In our study we did not collect this information, but it is important to consider in future research related to sport tourism.…”
Section: Discussionmentioning
confidence: 94%
“…Chinese tourists' leisure constraints have been studied fairly generally, such as in terms of their intentions to visit the United States (Lai et al, 2013). Others have examined these tourists' plans to travel to Norway (Mei & Lantai, 2018) or their decision making when arranging trips to Japan (Lin et al, 2017). Yet perceived constraints in special interest tourism (i.e., sex tourism) may differ from constraints in prior contexts.…”
Section: Introductionmentioning
confidence: 99%